2003
DOI: 10.1161/01.atv.0000083508.21989.15
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Endothelial Connexin37 and Connexin40 in Hyperlipidemic Mice

Abstract: Objective-We sought to clarify the response of endothelial connexins to hyperlipidemia and lipid-lowering therapy. Methods and Results-Aortic endothelial gap junctions were analyzed by en face immunoconfocal microscopy and electron microscopy in C57BL/6 mice subjected to the following regimens: (1) normal chow (NC) for 3 months (3 mo), (2) NC for 9 mo, (3) NC for 3 mo, followed by a cholesterol-enriched diet (CED) for 6 mo, (4) NC for 3 mo and CED for 6 mo, with simvastatin in the final week, and (5) (in apopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 42 publications
7
48
1
Order By: Relevance
“…A number of pathologies in which intercellular communication is disrupted are known where the gap-junction proteins Cxs are modified (11,21,27,28,31,41,53). In the present report, we first demonstrate that Cx37 and Cx40 protein expression were significantly lowered in coronary ECs isolated from diabetic mice when compared with ECs from control (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…A number of pathologies in which intercellular communication is disrupted are known where the gap-junction proteins Cxs are modified (11,21,27,28,31,41,53). In the present report, we first demonstrate that Cx37 and Cx40 protein expression were significantly lowered in coronary ECs isolated from diabetic mice when compared with ECs from control (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…GV oocytes were places on slides and fixed in methanol for 30 s and in 3.7% paraformaldehyde for 10 min. After blocking with 10% (v/v) normal goat serum for 1 h at 37°C, the slides were incubated with rabbit polyclonal anti-mouse Cx37 antibody (1:50) [24] at 4°C for overnight. All slides were gently agitated in three changes of PBS containing 0.1% (v/v) Tween-20 solution for 10 min each and then treated with FITC-conjugated goat antirabbit IgG (1:3000) (Vector Laboratories, Burlingame, CA) in 10% (v/v) normal goat serum for 1 h at room temperature.…”
Section: Immunofluorescent Localization Of Cx43 and Cx37mentioning
confidence: 99%
“…Yeh et al 26 characterized the effect of hypercholesteremia on aortic EC and found that Cx40 and Cx37 were both decreased and that a return to normal mouse chow diet rapidly brought Cx37 expression up to normal levels, whereas Cx40 levels remained decreased. Simon et al 27 demonstrated that injections of lipopolysaccharide into mice caused significant Cx40 downregulation in aortic EC compared with Cx37.…”
Section: Summary Of Changes In Connexin Expressionmentioning
confidence: 99%